Antioxidant capacity and phytochemical analysis of broccoli (Brassica oleracea L. var italica) powder with sun drying technology - Mazarina Devi; Soenar Soekopitojo; Laili Hidayati; Rendis Trisnawan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Broccoli (Brassica oleacea L. var italica) is classified as a valueable agricultural product that contains high quality active compounds. Broccoli can be damaged easily without proper handling and post-harvest processing. The purpose of this study was to determine the phytochemical content and antioxidant capacity of broccoli stems, leaves and flowers by sun drying method. The treated samples then analyzed for the phytochemical content and antioxidant capacity. Furthermore, the data obtained were analyzed using ANOVA and DMRT. The results showed that broccoli leaf powder had the highest content of vitamin C (7,673mg/100g), chlorophyll (1746,198mg/kg), vitamin K (226,423 µg/g), phenolics (24210,120 mg/kg), flavonoids (15239,947 mg/kg) and antioxidant capacity (IC50= 25,215 ppm) compared to flowers and stems. This study shows that sun drying process maintains the quality of the phytochemical content and antioxidant capacity of broccoli plants. It can be concluded that broccoli leaf powder has the highest phytochemical content and antioxidant capacity so it can be used as a food ingredient in food processing such as noodles and bread.